Removal of colour from semi-aerobic landfill leachate by solar photocatalytic / Salwa Mohd Zaini Makhtar …[et al.] - Mohd Zaini Makhtar, Salwa; Ibrahim, Naimah; Abd Ghani, Azlinda; Hasan, Masitah; Selimin, Mohammad Tamizi (2008)
Leachate are heavily polluted liquid which may contain large amount of chemical oxygen demand (COD), biological chemical demand (BOD), ammonia (NH3) and colour. This study was conducted to examine the percentage of colour removal using coagulation as pretreatment, followed by the effects of ZnO, pH, stirring time and solar photocatalytic as final treatment. The duration of photocatalic reaction occurs after 30 minutes of exposure to sunlight at solar intensity of 0.13 - 0.89 kW/m2 that is from 11 - 1 p.m. The study showed that, pretreatment of leachate by coagulation at no pH adjustment, at its natural pH 8.68 with addition 10 g/L FeCI3 as coagulant can remove 67.2% colour. But, 35% colour removal can be obtained by coagulation at pH 5 with addition 1 g/L FeCI3. Using 1.0 g/L ZnO at pH 5 capable of removing 97% colour after 120 minutes of exposure.